The Relationship Between Smoking Habits And Nutritional Status With Ari Incidence In The Working Area Of Onan Hasang Health Center, 2023 - Munthe, Seri Asnawati; Agnes N; Lia Rosa Veronika Sinaga; Jasmen Manurung (Akupun Tour Publisher, 2023)
ISPA can be caused by three factors, namely the individual's childhood factors, behavioral factors, and environmental factors. Individual childhood factors include: child's age, birth weight, nutritional status, vitamin A, and immunization status. Behavioral factors include behavior to prevent and control CI in infants, or the active role of the family/community in fighting CI. Environmental factors include: indoor air pollution (cigarette smoke and high concentrations of cooking fuel smoke), house ventilation and residential density (Prabu, 2009). The habit of parents smoking inside the house makes babies become passive smokers who are constantly exposed to cigarette smoke. Homes with parents who have smoking habits have the opportunity to increase the incidence of ARI by 7.83 times compared to homes where parents do not smoke in the house. Meanwhile, the number of smokers in the family is quite large (Rahmayatul, 2013). Onan Hasang Medical Center that ISPA is a disease that ranks in the top 10 every year, based on this, researchers are interested in conducting research. This type of research is quantitative with a cross-sectional design which aims to determine the relationship between nutritional status and smoking with the incidence of ISPA at the Onan Hasang Health Center in 2023. The population is all mothers who have toddlers who visit the Onan Hasang Health Center. The data will be processed using a computer and presented in a narrative and tabular manner and then analyzed using univariate and bivariate. The statistical test used is the chi-square test. After conducting research, it was found that there was a relationship between smoking and nutritional status with the incidence of ARI at the Onan Hasang Health Center, for this reason it was suggested that families avoid smoking and maintain the nutritional status of their children.